Combustion and emissions study on motorcycle engine fueled with butanol-gasoline blend. (September 2015) - Feng, Renhua; Fu, Jianqin; Yang, Jing; Wang, Yi; Li, Yangtao; Deng, Banglin; Liu, Jingping; Zhang, Daming
Abstract: In this paper, experimental studies were conducted on a single cylinder high speed spark ignition (SI) motorcycle engine under both full load and partial load at 6500 and 8500 rpm with pure gasoline, 30% and 35% volume butanol-gasoline blends. This study is trying to ﬁnd out the inﬂuence on combustion heat release of high speed SI engine by variables including ignition timing, butanol blend ratio and engine load. The results show that butanol-gasoline blend provides higher knocking resistance by allowing advance ignition timing in SI engines, which leads to more efﬁcient combustion. With butanol blend ratio increases, more complete combustion process will achieve with the optimum operating parameters. With engine load increases, the rates of heat release become faster and ascend in peak value for both pure gasoline and butanol-gasoline blends. Furthermore, engine performance parameters such as power, fuel economy and emissions have been compared and analyzed. The results also show that engine power, torque, brake specific energy consumption, HC, CO and O2 emissions are better than those of pure gasoline at full load with 35% volume butanol addition, combined with ignition timing optimization. But NOx and CO2 emissions are higher than those of the original level of pure gasoline. Highlights: Butanol-gasoline blend provides higher knocking resistance. Butanol-gasoline blend has more efficient combustion. Heat release rates slow down with engine load decreasing. Butanol-gasoline blend has better engine torque, BSEC, CO, HC and O2 emissions. NOx and CO2 emissions go up with butanol blend ratio.